Revenge of the Beta Boys: Opting out as an exercise in masculinity - Walker, Alicia (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This study examines the factors influencing underachieving boys on a high-performing high school campus. Unlike the “laddishness” often seen in studies of underachievement among boys, the boys in this study were quiet, unobtrusive, and compliant within the classroom. Using qualitative interviews and observations conducted over a one-year period, the study showed the formation of student identities in response to the hegemonic masculinity of the “golden boy” portrayed by the popular boys on campus, which included high academic performance. The boys constructed an alternate masculinity, the Beta Boy, designed to demonstrate superior intellect through eschewing in-class work and homework but performing particularly well on tests.